Identification of novel tumor microenvironment-associated genes in gastric cancer based on single-cell RNA-sequencing datasets - Wei, Xujin; Liu, Jie; Hong, Zhijun; Chen, Xin; Wang, Kang; Cai, Jianchun (Frontiers in Genetics, 2022)
Tumor microenvironment and heterogeneity play vital roles in the development and progression of gastric cancer (GC). In the past decade, a considerable amount of single-cell RNA-sequencing (scRNA-seq) studies have been published in the fields of oncology and immunology, which improve our knowledge of the GC immune microenvironment. However, much uncertainty still exists about the relationship between the macroscopic and microscopic data in transcriptomics. In the current study, we made full use of scRNA-seq data from the Gene Expression Omnibus database (GSE134520) to identify 25 cell subsets, including 11 microenvironment-related cell types. The MIF signaling pathway network was obtained upon analysis of receptor-ligand pairs and cell-cell interactions. By comparing the gene expression in a wide variety of cells between intestinal metaplasia and early gastric cancer, we identified 64 differentially expressed genes annotated as immune response and cellular communication. Subsequently, we screened these genes for prognostic clinical value based on the patients’ follow-up data from The Cancer Genome Atlas. TMPRSS15, VIM, APOA1, and RNASE1 were then selected for construction of LASSO risk scores and a nomogram model incorporating another five clinical risk factors was successfully created. The effectiveness of Least Absolute Shrinkage and Selection Operator risk scores was validated using Gene Set Enrichment Analysis and levels of immune cell infiltration. These findings will drive the development of prognostic evaluations affected by the immune tumor microenvironment in GC.